Development of a neighborhood drivability index and its association with transportation behavior in Toronto. (May 2022) - den Braver, Nicolette R.; Lakerveld, Jeroen; Gozdyra, Peter; van de Brug, Tim; Moin, John S.; Fazli, Ghazal S.; Rutters, Femke; Brug, Johannes; Moineddin, Rahim; Beulens, Joline W.J.; Booth, Gillian L.
Graphical abstract: Highlights: The drivability index included three factors: Urban sprawl, pedestrian facilities and parking. Residents in neighborhoods with a high drivability score had higher rates of car use than those in neighborhoods with a low drivability score. The association between neighborhood drivability and car use was strongest for short trips. The drivability of the neighborhood where people work is a strong determinant of car use. Abstract: Background: Car driving is a form of passive transport that is associated with an increase in physical inactivity, obesity, air pollution and noise. Built environment characteristics may influence transport mode choice, but comprehensive indices for built environment characteristics that drive car use are still lacking, while such an index could provide tangible policy entry points. Objective: We developed and validated a neighbourhood drivability index, capturing combined dimensions of the neighbourhood environment in the City of Toronto, and investigated its association with transportation choices (car, public transit or active transport), overall, by trip length, and combined for residential neighbourhood and workplace drivability. Methods: We used exploratory factor analysis to derive distinct factors (clusters of one or more environmental characteristics) that reflect the degree of car dependency in each neighbourhood, drawing from candidate variables that capture density, diversity, design, destination accessibility, distance to transit, and demand management. Area-level factor scores were then combined into a single composite score, reflecting neighbourhood drivability. Negative binomial generalized estimating equations were used to test the association between driveability quintiles (Q) and primary travel mode (>50% of trips by car, public transit, or walking/cycling) in a population-based sample of 63, 766 Toronto residents enrolled in the Transportation Tomorrow Survey (TTS) wave 2016, adjusting for individual and household characteristics, and accounting for clustering of respondents within households. Results: The drivability index consisted of three factors : Urban sprawl, pedestrian facilities and parking availability . Relative to those living in the least drivable neighbourhoods (Q1), those in high drivability areas (Q5) had a significantly higher rate of car travel (adjusted Risk Ratio (RR): 1.80, 95%CI: 1.77–1.88), and lower rate of public transit use (RR: 0.90, 95%CI: 0.85–0.94) and walking/cycling (RR: 0.22, 95%CI: 0.19–0.25). Associations were strongest for short trips (<3 km) (RR: 2.72, 95%CI: 2.48–2.92), and in analyses where both residential and workplace drivability was considered (RR for car use in high/high vs. low/low residential/workplace drivability: 2.18, 95%CI: 2.08–2.29). Conclusion: This novel neighbourhood drivability index predicted whether local residents drive or use active modes of transportation and can be used to investigate the association between drivability, physical activity, and chronic disease risk.